2023
DOI: 10.1186/s41021-023-00283-4
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA PVT1 induces apoptosis and inflammatory response of bronchial epithelial cells by regulating miR-30b-5p/BCL2L11 axis in COPD

Taoli Fu,
Hui Tian,
Hui Rong
et al.

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a serious health burden worldwide with high mortality. LncRNA plasmacytoma variant translocation 1 (PVT1) has been illustrated to serve as a biomarker for COPD progression. Nonetheless, its specific functions and mechanisms in COPD are unclarified. Methods Cigarette smoke extract (CSE) was utilized to stimulate 16HBE cells, and cigarette smoke combining with lipopolysaccharide (LPS) was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors found that there were some mistakes in the data for images of HE staining, and then replicated experiments and histological observations were performed again. The correct Fig.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors found that there were some mistakes in the data for images of HE staining, and then replicated experiments and histological observations were performed again. The correct Fig.…”
mentioning
confidence: 99%